XOTIRANING TURLARI VA ULARNING PSIXOLOGIK XUSUSIYATLARI (Multidisciplinary Journal of Science and Technology, 2026)
This article systematically investigates the complex structure of human memory and its psychological aspects. The article analyzes the main types of memory — sensory memory, short-term memory, long-term memory — and their functional differences, physiological foundations, and psychological mechanisms. The psychological characteristics of memory — encoding, storage, retrieval processes — and factors influencing them, such as attention, emotional state, repetition, as well as the neurophysiological causes of forgetting, are comprehensively covered in the article.